The Operating Performance Tests of Power Unit A1 in HPP "Zvornik" in Load-Frequency Control - Stanojčić, Vladimir S; Džepčeski, Dane; Arnautović, Dušan; Bogdanović, Slobodan; Pavlović, Jelena (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
The turbine-governing system characteristics derived from testing hydropower unit A1 in HPP “Zvornik” are presented. These tests give insights into the setup state and parameters of the governing system, as well as the qualitative analysis of load-frequency control response of the case study power unit within the power system of Serbia. Verification of relevant turbine-governing parameters was performed by direct application of appropriate standards and policies. The presented results can be used as a basis for the derivation of a turbine governor mathematical model and for a complete mathematical model of a hydropower unit as an element embedded in the power system.
Keywords: parameters; permanent droop; load frequency control; turbine governor